Primary large B-cell lymphoma of the central nervous system misdiagnosed as autoimmune encephalitis: a case report - Ren, Aihui; Zeng, Guanwen; Chen, Riling; Cao, Zhixing; Zhuo, Wenyan; Liang, Yubin (Frontiers in Oncology, 2025)
Primary central nervous system lymphomas (PCNSL) are rare, constituting 2 - 3% of intracranial malignancies. A 49-year-old male presented with a 20-day history of dizziness and a 15-day history of right-sided weakness. Physical examination revealed various abnormal signs. Initial cerebrospinal fluid (CSF) analysis was unremarkable, while MRI scans (both plain and contrast-enhanced) showed abnormal signals in the left brainstem, thalamus, and basal ganglia regions, with specific enhancement patterns, and arterial spin labeling (ASL) demonstrated hyperperfusion. The patient was initially diagnosed with autoimmune encephalitis (AE) and treated with methylprednisolone with dose reduction and subsequent discharge. However, two months later, his condition deteriorated. Re-evaluation of MRI data, along with magnetic resonance spectroscopy (MRS) results, suggested a neoplastic process. A stereotactic brain biopsy led to a PCNSL diagnosis. The patient was then transferred for high-dose methotrexate chemotherapy but due to lack of regular follow-up, the disease progressed, resulting in cerebral herniation and respiratory failure and ultimately death. The coexistence of PCNSL and AE is diagnostically difficult because of atypical clinical features and non-specific imaging. Thus, for patients with suspected CNS immune-mediated diseases who relapse after steroid treatment improvement, comprehensive evaluation including CSF examination, MRI, and prompt pathological examination is crucial to consider the possibility of PCNSL.